NURSING PRACTICE AND MODERN EDUCATION: CHALLENGES AND INNOVATIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Nursing, as a cornerstone of the healthcare system, has undergone significant transformation in recent decades. With rapid advancements in medical technologies, changing patient needs, and global health challenges, the role of nurses has become more complex and intellectually demanding. This paper explores the integration of modern educational strategies in nursing practice, analyzes existing challenges, and highlights innovative approaches to prepare future nurses for a dynamic healthcare environment.